Green human resource management and green creativity: Examining the role of green motivation in human resource management strategy - Setyanti, Sri Wahyu Lelly Hana; Yulisetiarini, Diah (International Journal of Management and Sustainability, 2025)
This study examines the influence of green Human Resource Management (HRM) practices on green creativity within Indonesia’s banking sector, with a specific focus on the mediating role of green motivation in HRM strategy. Employing a quantitative approach, the research utilizes SmartPLS 3.0 software and Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses and assess the indirect effect of green HRM on green creativity via green motivation. Data was collected from 200 banking sector employees using quota sampling. The results demonstrate that green HRM strategies significantly enhance green creativity among employees. Furthermore, green motivation was identified as a mediating mechanism linking green HRM practices to green creativity. This study underscores the critical role of green HRM strategies particularly green HRM initiatives and motivational factors in fostering green creativity within Indonesia’s banking industry. The findings offer significant theoretical and practical contributions by demonstrating how strategic implementation of green HRM practices can promote environmental sustainability in the banking sector. Practically, this study provides actionable insights for organizational stakeholders, highlighting how integrating green HRM policies with motivational mechanisms can effectively enhance green creativity among banking professionals.